Guliyeva , Tarana - (:unkn) unknown (My University, 2026)
Tarana Ali-Abbas Guliyeva graduated from the Faculty of Architecture of the Azerbaijan Civil Engineering Institute in 1983. Since 2005, she has been a faculty member of the Department of Fundamentals of Architecture at the Azerbaijan University of Architecture and Construction. She is the author of 34 scholarly works, including two course curricula, three methodological guides, one textbook, eight conference papers, and more than 20 scientific articles. Her current research focuses on the stylistic characteristics of Azerbaijan's architectural monuments.